Solder particles

Solder particles with a planar surface portion address the challenge of achieving reliable conductivity and insulation in miniaturized circuits by providing a wide contact area and improved wetting and spreading, resulting in enhanced connection stability.

JP2025069455APending Publication Date: 2025-04-30RESONAC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2025021206
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-01-30
Filing Date
2025-02-13
Publication Date
2025-04-30

Smart Images

  • Figure 2025069455000001_ABST
    Figure 2025069455000001_ABST
Patent Text Reader

Abstract

To provide solder particles capable of forming an anisotropic conductive material excellent in conduction reliability and insulation reliability.SOLUTION: Solder particles have a flat portion on a part of a surface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to solder particles. [Background technology]

[0002] Conventionally, the use of solder particles has been considered as conductive particles to be mixed into anisotropic conductive materials such as anisotropic conductive films, anisotropic conductive pastes, etc. For example, Patent Document 1 describes a conductive paste containing a thermosetting component and a plurality of solder particles that have been subjected to a specific surface treatment. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-76494 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, as circuit components have become finer, connections have become smaller, and the anisotropic conductive material is required to have higher electrical conductivity and insulation reliability. In order to ensure electrical conductivity and insulation reliability, the conductive particles contained in the anisotropic conductive material need to properly connect opposing electrodes, but this is not necessarily the case with conventional anisotropic conductive materials containing solder particles.

[0005] The present invention has been made in consideration of the above problems, and has an object to provide solder particles that can provide an anisotropic conductive material with excellent conductivity reliability and insulation reliability. [Means for solving the problem]

[0006] One aspect of the present invention relates to a solder particle having a flat portion on a part of its surface. By using such solder particles, it is possible to obtain an anisotropic conductive material having excellent electrical conductivity reliability and insulation reliability.

[0007] In one aspect, the average particle diameter of the solder particles may be 1 to 30 μm and the C.V. value may be 20% or less.

[0008] In one aspect, the ratio (A / B) of the diameter A of the flat portion to the diameter B of the solder particles may satisfy the following formula. 0.01 < A / B < 1.0

[0009] In one aspect, when a quadrilateral circumscribing the projection image of the solder particles is created by two pairs of parallel lines, if the distances between opposite sides are X and Y (where Y < X), X and Y may satisfy the following formula. 0.8 < Y / X < 1.0

[0010] In one aspect, the solder particles may contain at least one selected from the group consisting of tin, tin alloys, indium, and indium alloys.

[0011] In one aspect, the solder particles may contain at least one selected from the group consisting of In-Sn alloys, In-Sn-Ag alloys, In-Bi alloys, Sn-Au alloys, Sn-Bi alloys, Sn-Bi-Ag alloys, Sn-Ag-Cu alloys, and Sn-Cu alloys.

Advantages of the Invention

[0012] According to the present invention, there are provided solder particles capable of obtaining an anisotropic conductive material excellent in conduction reliability and insulation reliability.

Brief Description of the Drawings

[0013] [Figure 1] FIG. 1 is a diagram schematically showing an example of solder particles. [Diagram 2] FIG. 2 is a diagram showing the distances X and Y (where Y ≤ X) between opposite sides when a quadrilateral circumscribing the projection image of the solder particles is created by two pairs of parallel lines. [Diagram 3]FIG. 3(a) is a plan view showing a schematic diagram of an example of the base body, and FIG. 3(b) is a cross-sectional view taken along line IIIb-IIIb shown in FIG. 3(a). [Figure 4] 4(a) to (d) are cross-sectional views that diagrammatically show examples of the cross-sectional shape of a recess in a base body. [Diagram 5] FIG. 5 is a cross-sectional view that shows a schematic state in which solder particles are contained in recesses of a base. [Figure 6] FIG. 6 is a cross-sectional view that illustrates a state in which solder particles are formed in recesses of a base. [Figure 7] FIG. 7 is an SEM image of the solder particles obtained in Example 1. [Figure 8] FIG. 8 is a cross-sectional view that illustrates another example of the cross-sectional shape of the recess of the base body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described. The present invention is not limited to the following embodiment. The materials exemplified below may be used alone or in combination of two or more types, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. A numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage may be replaced by the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced by the value shown in the example.

[0015] <Solder particles> The solder particles according to this embodiment have a flat surface on a part of the surface. In this case, the surface other than the flat surface is preferably spherical crown-shaped. That is, the solder particles may have a flat surface and a curved surface part of the spherical crown. When an anisotropic conductive material is obtained using such solder particles, it is possible to realize excellent conductive reliability and insulating reliability. The reason for this will be explained below.

[0016] First, the flat surface of the solder particle contacts the electrode, thereby ensuring a large contact area between the flat surface and the electrode. For example, when connecting an electrode made of a material that the solder easily spreads on and an electrode made of a material that the solder does not easily spread on, the flat surface of the solder particle can be adjusted to be disposed on the latter electrode side, thereby enabling the connection between the two electrodes to be suitably performed.

[0017] In addition, the larger the contact area between the solder particles and the electrode, the easier it is for the solder to spread. For example, as a method for making the solder particles arranged on the electrode (substrate) wet and spread to the electrode, there is a method of applying flux to the solder particles themselves or the electrode in advance, and dissolving the solder particles by reflow (heating). In this case, if the oxide film of the solder particles is thick or the flux is weak, the solder is difficult to spread if the contact area between the solder particles and the electrode is small. On the other hand, if there is a flat part on a part of the surface of the solder particles, the contact area between the electrode and the solder particles becomes large, and the solder tends to spread easily. This is presumably because, when the oxide film is being removed, if the electrode and the solder particle surface come into contact, the thinned oxide film cracks, and the melted solder and flux flow, making it easier to remove the oxide film. In this way, if the contact area between the solder particles and the electrode is large, the number of contact points between the electrode and the solder particle surface increases, and the timing of wetting and spreading is accelerated, making it easier to wet and spread. In addition, since the solder particles are easily wetted and spread, the amount of flux can be reduced, and the occurrence of ion migration due to flux residue can be suppressed.

[0018] Furthermore, since the solder particles having a flat surface have good seating properties, when the solder particles are arranged on the electrodes so that the flat surface contacts the electrodes, the solder particles are unlikely to become displaced from their stable shape. In other words, it is easy to prevent the solder particles from rolling out of the space between the electrodes before reflow, which can cause a decrease in reliability of electrical continuity between opposing electrodes and a decrease in reliability of insulation between adjacent electrodes.

[0019] FIG. 1 is a diagram showing a schematic diagram of an example of a solder particle 1 according to the present embodiment. As shown in FIG. 1, the solder particle 1 has a shape in which a flat portion 11 of diameter A is formed on a part of the surface of a sphere having a diameter B. From the viewpoint of realizing excellent conductivity reliability and insulation reliability, the ratio (A / B) of the diameter A of the flat portion to the diameter B of the solder particle 1 is set to, for example, more than 0.01 and less than 1.0 (0.01 Specifically, any particle is observed with a scanning electron microscope and an image is taken. From the image obtained, the diameter B of the solder particle and the diameter A of the flat surface are measured and the A / B of the particle is calculated. This procedure is performed on 300 solder particles and the average value is calculated to be the A / B of the solder particle.

[0020] The solder particles 1 may have an average particle diameter of 1 to 30 μm and a CV value of 20% or less. Such solder particles have both a small average particle diameter and a narrow particle size distribution, and can be suitably used as conductive particles for anisotropic conductive materials with high conductive and insulating reliability.

[0021] The average particle size of the solder particles is not particularly limited as long as it is within the above range, but is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. The average particle size of the solder particles is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 4 μm or more.

[0022] ​The average particle size of the solder particles can be measured using various methods suited to the size. For example, dynamic light scattering, laser diffraction, centrifugal sedimentation, electrical sensing zone method, resonance mass measurement method, etc. can be used. Furthermore, a method can be used to measure the particle size from images obtained by an optical microscope, an electron microscope, etc. Specific devices include a flow type particle image analyzer, a microtrack, a Coulter counter, etc.

[0023] From the viewpoint of realizing better conductive reliability and insulating reliability, the CV value of the solder particles is preferably 20% or less, more preferably 10% or less, further preferably 7% or less, and most preferably 5% or less. In addition, there is no particular limit to the lower limit of the CV value of the solder particles. For example, the CV value of the solder particles may be 1% or more, or may be 2% or more.

[0024] The CV value of the solder particles is calculated by dividing the standard deviation of the particle diameter measured by the above-mentioned method by the average particle diameter, and multiplying the result by 100.

[0025] When a quadrilateral circumscribing the projection image of a solder particle is created by two pairs of parallel lines, when the distances between opposite sides are X and Y (where Y < X), the ratio of Y to X (Y / X) may be greater than 0.8 and less than 1.0 (0.8 < Y / X < 1.0), and may be between 0.81 and 0.99. Such solder particles can be said to be particles closer to a perfect sphere. When the solder particles are accommodated again in the concave portion 62 of the substrate 60, if the solder particles are close to a spherical shape, there is a tendency to be easily accommodated. Also, because the solder particles are close to a perfect sphere, when electrically connecting a plurality of opposing electrodes via the solder particles, unevenness in contact between the solder particles and the electrodes is less likely to occur, and a stable connection tends to be obtained. Further, when producing a conductive film or paste in which the solder particles are dispersed in a resin material, high dispersibility is obtained, and dispersion stability during production tends to be obtained. Furthermore, when a film or paste in which the solder particles are dispersed in a resin material is used for connection between electrodes, even if the solder particles rotate in the resin, if the solder particles are spherical, when viewed in the projection image, the projected areas of the solder particles are close to each other. Therefore, there is a tendency to easily obtain a stable electrical connection with less variation when connecting the electrodes to each other.

[0026] Figure 2 is a diagram showing the distances X and Y (where Y < X) between opposite sides when a quadrilateral circumscribing the projection image of a solder particle is created by two pairs of parallel lines. For example, an arbitrary particle is observed with a scanning electron microscope to obtain a projection image. Two pairs of parallel lines are drawn for the obtained projection image. One pair of parallel lines is arranged at the position where the distance between the parallel lines is the minimum, and the other pair of parallel lines is arranged at the position where the distance between the parallel lines is the maximum, and Y / X of the particle is obtained. This operation is performed on 300 solder particles to calculate the average value, which is taken as Y / X of the solder particles.

[0027] The solder particles may contain tin or a tin alloy. As the tin alloy, for example, In - Sn alloy, In - Sn - Ag alloy, Sn - Au alloy, Sn - Bi alloy, Sn - Bi - Ag alloy, Sn - Ag - Cu alloy, Sn - Cu alloy, etc. can be used. Specific examples of these tin alloys are as follows. ·In - Sn (In 52 mass%, Bi 48 mass%, melting point 118°C) ·In-Sn-Ag (In20% by mass, Sn77.2% by mass, Ag2.8% by mass, melting point 175℃) Sn-Bi (Sn 43% by mass, Bi 57% by mass, melting point 138°C) · Sn-Bi-Ag (Sn 42% by mass, Bi 57% by mass, Ag 1% by mass, melting point 139°C) · Sn-Ag-Cu (Sn 96.5% by mass, Ag 3% by mass, Cu 0.5% by mass, melting point 217°C) Sn-Cu (Sn 99.3% by mass, Cu 0.7% by mass, melting point 227°C) ·Sn-Au (Sn21.0% by mass, Au79.0% by mass, melting point 278℃) The solder particles may contain indium or an indium alloy. Examples of the indium alloy include an In-Bi alloy and an In-Ag alloy. Specific examples of these indium alloys include the following. In-Bi (In 66.3 mass%, Bi 33.7 mass%, melting point 72°C) In-Bi (In 33.0 mass%, Bi 67.0 mass%, melting point 109°C) In-Ag (In 97.0% by mass, Ag 3.0% by mass, melting point 145°C)

[0028] The above tin alloy or indium alloy can be selected depending on the application of the solder particles (temperature during use), etc. For example, when the solder particles are used for low-temperature fusion, an In-Sn alloy or an Sn-Bi alloy can be used, and in this case, fusion can be performed at 150°C or less. When a material with a high melting point such as an Sn-Ag-Cu alloy or an Sn-Cu alloy is used, high reliability can be maintained even after exposure to high temperatures.

[0029] The solder particles may contain one or more elements selected from Ag, Cu, Ni, Bi, Zn, Pd, Pb, Au, P, and B. Of these elements, Ag or Cu may be contained for the following reasons: When the solder particles contain Ag or Cu, the melting point of the solder particles can be lowered to about 220°C, and the bonding strength with the electrodes is further improved, making it easier to obtain better electrical connection reliability.

[0030] The Cu content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. When the Cu content is 0.05 mass% or more, better solder connection reliability is easily achieved. When the Cu content is 10 mass% or less, the solder particles tend to have a low melting point and excellent wettability, and as a result, the connection reliability of the joints formed by the solder particles tends to be good.

[0031] The Ag content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. When the Ag content is 0.05 mass% or more, better solder connection reliability is easily achieved. Also, when the Ag oil content is 10 mass% or less, the solder particles tend to have a low melting point and excellent wettability, and as a result, the connection reliability of the joints formed by the solder particles tends to be good.

[0032] The use of the solder particles is not particularly limited, and for example, they can be suitably used as conductive particles for anisotropic conductive materials. They can also be suitably used for applications such as electrically connecting electrodes together in a ball grid array connection method (BGA connection) that is widely used in the mounting of semiconductor integrated circuits, sealing or sealing parts such as MEMS, brazing, and spacers for controlling height and gap. In other words, the solder particles can be used in general applications where solder has been used in the past.

[0033] <Method of manufacturing solder particles> The method for manufacturing the solder particles according to the present embodiment is not particularly limited, but an example of the manufacturing method will be described below. For example, the solder particles according to the present embodiment can be manufactured by a method for manufacturing solder particles including a preparation step of preparing a base having a plurality of recesses and solder particles, a housing step of housing at least some of the solder particles in the recesses of the base, and a fusion step of fusing the solder particles housed in the recesses to form solder particles inside the recesses. According to this manufacturing method, solder particles having a flat portion on a part of the surface are manufactured.

[0034] Hereinafter, the method for producing the solder particles will be described with reference to FIGS.

[0035] First, solder particles and a base 60 for accommodating the solder particles are prepared. FIG. 3(a) is a plan view showing a schematic diagram of an example of the base 60, and FIG. 3(b) is a cross-sectional view taken along line IIIb-IIIb shown in FIG. 3(a). The base 60 shown in FIG. 3(a) has a plurality of recesses 62. The plurality of recesses 62 may be regularly arranged in a predetermined pattern. In this case, after the solder particles are formed in the recesses 62, the solder particles in the recesses 62 can be transferred to a resin material or the like, thereby allowing the solder particles to be regularly arranged.

[0036] The recess 62 of the base 60 is preferably formed in a tapered shape with an opening area expanding from the bottom 62a of the recess 62 toward the surface 60a of the base 60. That is, as shown in Fig. 3, the width of the bottom 62a of the recess 62 (width a in Fig. 3) is preferably narrower than the width of the opening on the surface 60a of the recess 62 (width b in Fig. 3). The size of the recess 62 (width a, width b, volume, taper angle, depth, etc.) may be set according to the size of the desired solder particles.

[0037] The shape of the recess 62 may be a shape other than the shape shown in Fig. 3. For example, the shape of the opening in the surface 60a of the recess 62 may be an ellipse, a triangle, a rectangle, a polygon, etc., other than the circle as shown in Fig. 3.

[0038] The shape of the recess 62 in a cross section perpendicular to the surface 60a may be, for example, a shape as shown in FIG. 4. FIGS. 4(a) to (d) are cross-sectional views that typically show examples of the cross-sectional shapes of the recesses of the base. The bottom surface of each of the cross-sectional shapes shown in FIGS. 4(a) to (d) is flat. This forms a flat portion on a part of the surface of the solder particle. In addition, in each of the cross-sectional shapes shown in FIGS. 4(a) to (d), the width (width b) of the opening of the recess 62 on the surface 60a is the maximum width in the cross-sectional shape. This makes it easier to remove the solder particles formed in the recess 62, improving workability.

[0039] Materials that can be used to form the base 60 include inorganic materials such as silicon, various ceramics, glass, and metals such as stainless steel, as well as organic materials such as various resins. Of these, the base 60 is preferably made of a heat-resistant material that does not change at the melting temperature of the solder particles. The recesses 62 of the base 60 can be formed by known methods such as photolithography, imprinting, mechanical processing, electron beam processing, and radiation processing.

[0040] The solder particles prepared in the preparation step may include particles having a particle diameter smaller than the width (width b) of the opening in surface 60a of recess 62, and preferably include more particles having a particle diameter smaller than width b. For example, the solder particles preferably have a D10 particle diameter in the particle size distribution smaller than width b, more preferably a D30 particle diameter in the particle size distribution smaller than width b, and even more preferably a D50 particle diameter in the particle size distribution smaller than width b.

[0041] The particle size distribution of the solder particles can be measured using various methods suited to the size. For example, dynamic light scattering, laser diffraction, centrifugal sedimentation, electrical sensing zone method, resonance mass measurement method, etc. can be used. Furthermore, a method can be used to measure the particle size from images obtained by an optical microscope, an electron microscope, etc. Specific devices include a flow type particle image analyzer, a microtrack, a Coulter counter, etc.

[0042] Although the CV value of the solder particles prepared in the preparation step is not particularly limited, a high CV value is preferable from the viewpoint of improving the filling property of the combination of large and small particles into the recesses 62. For example, the CV value of the solder particles may exceed 20%, is preferably 25% or more, and is more preferably 30% or more.

[0043] The CV value of the solder fine particles is calculated by dividing the standard deviation of the particle diameter measured by the above-mentioned method by the average particle diameter (D50 particle diameter) and multiplying the result by 100.

[0044] The solder particles may contain tin or a tin alloy. Examples of the tin alloy include an In-Sn alloy, an In-Sn-Ag alloy, an Sn-Au alloy, an Sn-Bi alloy, an Sn-Bi-Ag alloy, an Sn-Ag-Cu alloy, and an Sn-Cu alloy. Specific examples of these tin alloys include the following: In-Sn (In 52% by mass, Bi 48% by mass, melting point 118°C) ·In-Sn-Ag (In20% by mass, Sn77.2% by mass, Ag2.8% by mass, melting point 175℃) Sn-Bi (Sn 43% by mass, Bi 57% by mass, melting point 138°C) · Sn-Bi-Ag (Sn 42% by mass, Bi 57% by mass, Ag 1% by mass, melting point 139°C) · Sn-Ag-Cu (Sn 96.5% by mass, Ag 3% by mass, Cu 0.5% by mass, melting point 217°C) Sn-Cu (Sn 99.3% by mass, Cu 0.7% by mass, melting point 227°C) ·Sn-Au (Sn21.0% by mass, Au79.0% by mass, melting point 278℃) The solder particles may contain indium or an indium alloy. Examples of the indium alloy include an In-Bi alloy and an In-Ag alloy. Specific examples of these indium alloys include the following. In-Bi (In 66.3 mass%, Bi 33.7 mass%, melting point 72°C) In-Bi (In 33.0 mass%, Bi 67.0 mass%, melting point 109°C) In-Ag (In 97.0% by mass, Ag 3.0% by mass, melting point 145°C)

[0045] The above tin alloy or indium alloy can be selected depending on the application of the solder particles (temperature during use), etc. For example, when it is desired to obtain solder particles for use in low-temperature fusion, an In-Sn alloy or an Sn-Bi alloy can be used, and in this case, solder particles that can be fused at 150° C. or less can be obtained. When a material with a high melting point, such as an Sn-Ag-Cu alloy or an Sn-Cu alloy, is used, solder particles that can maintain high reliability even after being left at high temperatures can be obtained.

[0046] The solder fine particles may contain one or more elements selected from Ag, Cu, Ni, Bi, Zn, Pd, Pb, Au, P, and B. Of these elements, Ag or Cu may be contained for the following reasons: When the solder fine particles contain Ag or Cu, the melting point of the resulting solder particles can be lowered to about 220°C, and good electrical reliability can be obtained by obtaining solder particles with excellent bonding strength with the electrodes.

[0047] The Cu content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. When the Cu content is 0.05 mass% or more, solder particles that can achieve good solder connection reliability are easily obtained. When the Cu content is 10 mass% or less, solder particles that have a low melting point and excellent wettability are easily obtained, and as a result, the connection reliability of the joints formed by the solder particles is easily good.

[0048] The Ag content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. If the Ag content is 0.05 mass% or more, it is easy to obtain solder particles that can achieve good solder connection reliability. Also, if the Ag oil content is 10 mass% or less, it is easy to obtain solder particles that have a low melting point and excellent wettability, and as a result, the connection reliability of the joints formed by the solder particles is easy to be good.

[0049] In the accommodation step, the solder particles prepared in the preparation step are accommodated in each of the recesses 62 of the base 60. The accommodation step may be a step in which all of the solder particles prepared in the preparation step are accommodated in the recesses 62, or a step in which only a portion of the solder particles prepared in the preparation step (for example, solder particles smaller than the opening width b of the recesses 62) are accommodated in the recesses 62.

[0050] Fig. 5 is a cross-sectional view that shows a schematic state in which solder particles 111 are accommodated in recesses 62 of base 60. As shown in Fig. 5, a plurality of solder particles 111 are accommodated in each of a plurality of recesses 62.

[0051] The amount of solder particles 111 accommodated in recess 62 is, for example, preferably 20% or more, more preferably 30% or more, even more preferably 50% or more, and most preferably 60% or more of the volume of recess 62. This reduces variation in the amount accommodated, making it easier to obtain solder particles with a smaller particle size distribution.

[0052] The method of storing the solder particles in the recesses 62 is not particularly limited. The storing method may be either a dry method or a wet method. For example, the solder particles prepared in the preparation step are placed on the base 60, and a squeegee is used to rub the surface 60a of the base 60, thereby removing excess solder particles and storing sufficient solder particles in the recesses 62. If the width b of the opening of the recesses 62 is greater than the depth of the recesses 62, the solder particles may protrude from the opening of the recesses 62. If a squeegee is used, the solder particles protruding from the opening of the recesses 62 are removed. Other methods for removing excess solder particles include blowing compressed air or rubbing the surface 60a of the substrate 60 with a nonwoven fabric or a bundle of fibers. These methods are preferable for handling solder particles that are easily deformed because they exert a weaker physical force than a squeegee. These methods also make it possible to leave the solder particles protruding from the opening of the recess 62 inside the recess.

[0053] The fusion process is a process in which the solder particles 111 contained in the recesses 62 are fused to form solder particles 1 inside the recesses 62. FIG. 6 is a cross-sectional view that shows a schematic state in which the solder particles 1 are formed in the recesses 62 of the base 60. The solder particles 111 contained in the recesses 62 are unified by melting, and become spherical due to surface tension. At this time, at the contact portion with the bottom 62a of the recesses 62, the molten solder follows the bottom 62a to form a flat portion 11. As a result, the formed solder particle 1 has a shape having a flat portion 11 on part of its surface.

[0054] FIG. 1 is a view of the solder particle 1 as viewed from the side opposite to the opening of the recess 62 in FIG.

[0055] As a method for melting the solder particles 111 accommodated in the recess 62, there is a method of heating the solder particles 111 to a temperature equal to or higher than the melting point of the solder. The solder particles 111 may not melt, wet, or spread even when heated to a temperature equal to or higher than the melting point due to the influence of an oxide film. For this reason, the solder particles 111 can be melted, wet, spread, and unified by exposing the solder particles 111 to a reducing atmosphere, removing the surface oxide film of the solder particles 111, and then heating the solder particles 111 to a temperature equal to or higher than the melting point of the solder particles 111. In addition, it is preferable to melt the solder particles 111 in a reducing atmosphere. By heating the solder particles 111 to a temperature equal to or higher than the melting point of the solder particles 111 and creating a reducing atmosphere, the oxide film on the surface of the solder particles 111 is reduced, and the melting, wet, spread, and unification of the solder particles 111 can be efficiently promoted.

[0056] The method for creating a reducing atmosphere is not particularly limited as long as the above-mentioned effects can be obtained, and examples of the method include a method using hydrogen gas, hydrogen radicals, formic acid gas, etc. For example, the solder particles 111 can be melted in a reducing atmosphere by using a hydrogen reduction furnace, a hydrogen radical reduction furnace, a formic acid reduction furnace, or a conveyor furnace or continuous furnace thereof. These devices may be equipped with a heating device, a chamber for filling an inert gas (nitrogen, argon, etc.), a mechanism for evacuating the chamber, etc., in the furnace, which makes it easier to control the reducing gas. In addition, if the chamber can be evacuated, voids can be removed by reducing the pressure after the solder particles 111 are melted and unified, and solder particles 1 with even more excellent connection stability can be obtained.

[0057] The profile of the reduction of the solder particles 111, the melting conditions, the temperature, the adjustment of the atmosphere in the furnace, etc. may be appropriately set in consideration of the melting point, particle size, recess size, and material of the base 60 of the solder particles 111 of the solder particles 111. For example, the base 60 having the recesses filled with the solder particles 111 is inserted into a furnace, and after evacuation, a reducing gas is introduced to fill the furnace with the reducing gas, the surface oxide film of the solder particles 111 is removed, and the reducing gas is removed by evacuation, and then the furnace is heated to a temperature equal to or higher than the melting point of the solder particles 111 to melt and coalesce the solder particles to form solder particles in the recesses 62. After that, nitrogen gas is filled and the temperature in the furnace is returned to room temperature to obtain the solder particles 1. Also, for example, the base 60 with the solder particles 111 filled in the recesses is inserted into a furnace, and after evacuation, reducing gas is introduced to fill the furnace with the reducing gas, the solder particles 111 are heated by an in-furnace heater to remove the surface oxide film of the solder particles 111, and then the reducing gas is removed by evacuation, and then the solder particles 111 are heated to a temperature equal to or higher than the melting point thereof to melt and coalesce the solder particles to form solder particles in the recesses 62, and then nitrogen gas is filled in and the temperature inside the furnace is returned to room temperature to obtain the solder particles 1. Heating the solder particles in a reducing atmosphere has the advantage of increasing the reducing power and making it easier to remove the surface oxide film of the solder particles.

[0058] Furthermore, for example, the base 60 with the solder particles 111 filled in the recesses is inserted into a furnace, and after evacuation, reducing gas is introduced to fill the furnace with the reducing gas, and the base 60 is heated by an in-furnace heater to above the melting point of the solder particles 111, the oxide film on the surface of the solder particles 111 is removed by reduction while at the same time the solder particles are melted and unified to form solder particles in the recesses 62, the reducing gas is removed by evacuation, and the voids in the solder particles are further reduced, after which nitrogen gas is filled and the temperature inside the furnace is returned to room temperature to obtain the solder particles 1. In this case, the temperature inside the furnace only needs to be increased and decreased once each, which has the advantage of allowing processing in a short time.

[0059] After the solder particles are formed in the recess 62, the furnace is once again made into a reducing atmosphere, and a process is added to remove any remaining surface oxide film, thereby reducing residues such as solder particles that remain unfused and parts of the oxide film that remain unfused.

[0060] When an atmospheric pressure conveyor furnace is used, the base 60 with the recesses filled with the solder particles 111 can be placed on a conveyor and passed through multiple zones in succession to obtain the solder particles 1. For example, the base 60 with the recesses filled with the solder particles 111 can be placed on a conveyor set to a constant speed, passed through a zone filled with an inert gas such as nitrogen or argon at a temperature lower than the melting point of the solder particles 111, then passed through a zone containing a reducing gas such as formic acid gas at a temperature lower than the melting point of the solder particles 111 to remove the surface oxide film of the solder particles 111, then passed through a zone filled with an inert gas such as nitrogen or argon at a temperature higher than the melting point of the solder particles 111 to melt and coalesce the solder particles 111, and then passed through a cooling zone filled with an inert gas such as nitrogen or argon to obtain the solder particles 1. For example, the base 60 with the solder particles 111 filled in the recesses is placed on a conveyer set at a constant speed, passed through a zone filled with an inert gas such as nitrogen or argon at a temperature equal to or higher than the melting point of the solder particles 111, and then passed through a zone where a reducing gas such as formic acid gas at a temperature equal to or higher than the melting point of the solder particles 111 is present, to remove the surface oxide film of the solder particles 111, melt and unify them, and then passed through a cooling zone filled with an inert gas such as nitrogen or argon to obtain solder particles 1. Since the conveyer furnace can perform processing at atmospheric pressure, it is also possible to continuously process a film-like material by roll-to-roll. For example, a continuous roll product of the base 60 with the solder particles 111 filled in the recesses is produced, and a roll unwinder is installed at the entrance side of the conveyer furnace and a roll winder is installed at the exit side of the conveyer furnace, and the base 60 is transported at a constant speed and passed through each zone in the conveyer furnace, thereby fusing the solder particles 111 filled in the recesses.

[0061] The formed solder particles 1 may be transported, stored, etc. in a state where they are accommodated in the recesses 62 of the base 60, or may be removed from the recesses 62 and collected.

[0062] Alternatively, a resin material may be placed on the surface 60a of the base 60, and the solder particles 1 in the recesses 62 may be transferred to the resin material. In this case, if the recesses 62 are regularly arranged, the solder particles 1 can be regularly arranged on the resin material. In this case, the planar portions of the arranged solder particles 1 can be maintained in one direction. Therefore, the planar portions are effectively utilized when connecting the electrodes, and it is easy to enjoy the advantages of ensuring a wide contact area between the solder particles and the electrodes and suppressing the positional deviation of the solder particles, as described above.

[0063] The manufacturing method of this embodiment can form solder particles of uniform size regardless of the material and shape of the solder particles. For example, indium-based solder can be deposited by plating, but it is difficult to deposit in a particulate form, and it is soft and difficult to handle. However, in the manufacturing method of this embodiment, indium-based solder particles are used as a raw material, so that indium-based solder particles having a uniform particle size can be easily manufactured. In addition, since the formed solder particles 1 can be handled in a state where they are accommodated in the recesses 62 of the base 60, they can be transported and stored without being deformed. Furthermore, since the formed solder particles 1 are simply accommodated in the recesses 62 of the base 60, they can be easily taken out, and they can be collected and surface-treated without being deformed.

[0064] Furthermore, the solder particles 111 may have a large variation in particle size distribution or may have an irregular shape, and as long as they can be contained within the recesses 62, they can be used as a raw material in the manufacturing method of this embodiment.

[0065] Furthermore, in the manufacturing method of this embodiment, the shape of the recesses 62 of the base 60 can be freely designed by lithography, imprinting, electron beam processing, radiation processing, mechanical processing, etc. Since the size of the solder particles 1 depends on the amount of solder fine particles 111 contained in the recesses 62, in the manufacturing method of this embodiment, the size of the solder particles 1 can be freely designed by designing the recesses 62.

[0066] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0068] <Preparation of solder particles> [Example 1] (Step a1: Classification of solder particles) 100g of Sn-Bi solder particles (5N Plus, melting point 139℃, Type 8) were immersed in distilled water, ultrasonically dispersed, and then left to stand, and the solder particles floating in the supernatant were collected. This process was repeated to collect 10g of solder particles. The average particle size of the obtained solder particles was 1.0μm, and the CV value was 42%. (Step b1: Arrangement on a substrate) A substrate (polyimide film, 100 μm thick) was prepared that had multiple recesses with an opening diameter of 1.2 μmφ, a bottom diameter of 1.0 μmφ, and a depth of 1.0 μm (the bottom diameter of 1.0 μmφ is located in the center of the opening diameter of 1.2 μmφ when the opening is viewed from above). The multiple recesses were regularly arranged at intervals of 1.0 μm. The solder particles (average particle diameter 1.0 μm, CV value 42%) obtained in step a were placed in the recesses of the substrate. The surface of the substrate on which the recesses were formed was rubbed with a slightly adhesive roller to remove excess solder particles, and a substrate was obtained in which the solder particles were placed only in the recesses. (Step c1: Formation of solder particles) The substrate with the solder particles placed in the recesses in step b1 was placed in a hydrogen reduction furnace, and after evacuation, hydrogen gas was introduced into the furnace to fill it with hydrogen. The furnace was then kept at 280°C for 20 minutes, after which it was evacuated again, nitrogen was introduced to return the pressure to atmospheric pressure, and the temperature inside the furnace was then lowered to room temperature to form the solder particles.

[0069] The substrate after step c1 was tapped from the back side of the recess to recover the solder particles from the recess. The obtained solder particles were observed by the following method. The obtained solder particles were placed on a conductive tape fixed to the surface of a scanning electron microscope (SEM) observation stand, and the SEM observation stand was tapped on a 5 mm thick stainless steel plate to spread the solder particles evenly on the conductive tape. Thereafter, compressed nitrogen gas was sprayed onto the surface of the conductive tape to fix the solder particles in a single layer on the conductive tape. The observation results are shown in FIG. 7. FIG. 7 is an SEM image of the solder particles obtained in Example 1. As shown in the figure, the obtained solder particles had a shape in which a flat portion was formed on part of the surface of a sphere. The solder particles obtained in other Examples also had the same shape.

[0070] [Examples 2 to 12] Solder particles were produced in the same manner as in Example 1, except that the recess size was changed as shown in Table 1.

[0071] <Example 13> Except for carrying out the following step c2 instead of step c1, solder particles were produced, collected, and evaluated in the same manner as in Example 1. The results are shown in Table 2. (Step c2) Formation of solder particles The substrate with the solder particles placed in the recesses in step b1 was placed in a hydrogen radical reduction furnace (plasma reflow device manufactured by Shinko Seiki Co., Ltd.), and after evacuation, hydrogen gas was introduced into the furnace to fill it with hydrogen gas. The temperature inside the furnace was then adjusted to 120°C, and hydrogen radicals were irradiated for 5 minutes. The hydrogen gas in the furnace was then removed by evacuation, and the furnace was heated to 170°C. After that, nitrogen was introduced into the furnace to return it to atmospheric pressure, and the temperature inside the furnace was then lowered to room temperature to form solder particles.

[0072] <Examples 14 to 24> Solder particles were produced, collected and evaluated in the same manner as in Example 13, except that the size of the recesses was changed as shown in Table 1. The results are shown in Table 2.

[0073] <Example 25> Except for carrying out the following step c2 instead of step c1, solder particles were produced, collected, and evaluated in the same manner as in Example 1. The results are shown in Table 2. (Step c2) Formation of solder particles The substrate with the solder particles placed in the recesses in step b1 was placed in a hydrogen radical reduction furnace (plasma reflow device manufactured by Shinko Seiki Co., Ltd.), and after evacuation, hydrogen gas was introduced into the furnace to fill it with hydrogen gas. The temperature inside the furnace was then adjusted to 120°C, and hydrogen radicals were irradiated for 5 minutes. The hydrogen gas in the furnace was then removed by evacuation, and the furnace was heated to 145°C. After that, nitrogen was introduced into the furnace to return it to atmospheric pressure, and the temperature inside the furnace was then lowered to room temperature to form solder particles.

[0074] <Examples 26 to 36> Solder particles were produced, collected and evaluated in the same manner as in Example 25, except that the size of the recessed portion was changed as shown in Table 1. The results are shown in Table 2.

[0075] <Preparation of anisotropic conductive film> [Preparation Example 1] (Step d1: Filling the recess with flux) A coating solution was prepared by dissolving 10 g of adipic acid in 200 g of toluene, and this was applied to the base (transfer mold) in which the solder particles were placed in the recesses in step c1. Excess coating solution was then removed using a squeegee, and the recesses were filled with the coating solution. This was then placed in an explosion-proof dryer at 80°C for 1 minute to vaporize the toluene, filling the recesses with adipic acid, a flux component. (Step e1: Preparation of adhesive film) 100g of phenoxy resin (manufactured by Union Carbide, trade name "PKHC") and 75g of acrylic rubber (a copolymer of 40 parts by mass of butyl acrylate, 30 parts by mass of ethyl acrylate, 30 parts by mass of acrylonitrile, and 3 parts by mass of glycidyl methacrylate, molecular weight: 850,000) were dissolved in 400g of ethyl acetate to obtain a solution. 300g of liquid epoxy resin (epoxy equivalent 185, manufactured by Asahi Kasei Epoxy Corporation, trade name "Novacure HX-3941") containing a microcapsule type latent hardener was added to this solution and stirred to obtain an adhesive solution. The obtained adhesive solution was applied to a separator (a silicone-treated polyethylene terephthalate film, thickness 40 μm) using a roll coater, and dried by heating at 90 ° C for 10 minutes to produce adhesive films (insulating resin films) with thicknesses of 4, 6, 8, 12, and 20 μm on the separator. (Step f1: Transfer of solder particles) The adhesive film formed on the separator and the base (transfer mold) on which the solder particles with flux obtained in step d1 were arranged were placed face to face, and the solder particles were transferred to the adhesive film. (Step g1: Preparation of anisotropic conductive film) The adhesive film prepared in the same manner as in step e1 is brought into contact with the transfer surface of the adhesive film obtained in step f1, and then subjected to pressure of 50°C, 0.1 MPa (1 kgf / cm 2 ), an anisotropic conductive film was obtained in which, in a cross-sectional view of the film, the solder particles were arranged in layers and the flat portions of the solder particles faced only one of the main surfaces of the film. Anisotropic conductive films with thicknesses of 8 μm, 12 μm, 16 μm, 24 μm, and 40 μm were produced by overlapping 4 μm on a 4 μm thick film, and similarly overlapping 6 μm on a 6 μm film, 8 μm on an 8 μm film, 12 μm on a 12 μm film, and 20 μm on a 20 μm film.

[0076] [Evaluation of solder particles] The adhesive film obtained by Process f1 was cut out into pieces of 10 cm × 10 cm. After Pt sputtering was performed on the surface where the solder particles were arranged, SEM observation was carried out. 300 solder particles were observed, and the average diameter B (average particle diameter), the average diameter A of the flat part, the C.V. value, the circularity, A / B, and Y / X were calculated. The results are shown in Table 2. Circularity: The ratio r / R of the radii of two concentric circles (the radius r of the minimum circumscribed circle and the radius R of the maximum inscribed circle) of the solder particle. A / B: The ratio of the diameter A of the flat part to the diameter B of the solder particle. Y / X: In the case where a quadrilateral circumscribing the projection image of the solder particle is created by two pairs of parallel lines, the ratio of Y to X when the distances between the opposing sides are defined as X and Y (where Y < X).

[0077] <Fabrication of the Connection Structure> (Process h1: Preparation of the Chip with Copper Bumps) Five types of chips with copper bumps (1.7 × 1.7 mm, thickness: 0.5 mm) shown below were prepared. · Chip C1… Area 30 μm × 30 μm, space 30 μm, height: 10 μm, number of bumps 362 · Chip C2… Area 15 μm × 15 μm, space 10 μm, height: 10 μm, number of bumps 362 · Chip C3… Area 10 μm × 10 μm, space 10 μm, height: 7 μm, number of bumps 362 · Chip C4… Area 5 μm × 5 μm, space 6 μm, height: 5 μm, number of bumps 362 · Chip C5… Area 3 μm × 3 μm, space 3 μm, height: 5 μm, number of bumps 362 (Process i1: Preparation of the Substrate with Copper Bumps) Five types of substrates with copper bumps (thickness: 0.7 mm) shown below were prepared. · Substrate D1… Area 30 μm × 30 μm, space 30 μm, height: 10 μm, number of bumps 362 · Substrate D2… Area 15 μm × 15 μm, space 10 μm, height: 10 μm, number of bumps 362 · Substrate D3… Area 10 μm × 10 μm, space 10 μm, height: 7 μm, number of bumps 362 Substrate D4: Area 5μm×5μm, space 6μm, height 5μm, number of bumps 362 Substrate D5: Area 3μm×3μm, space 3μm, height: 5μm, number of bumps 362 (Step j1: Connecting a chip with copper bumps to a substrate with copper bumps) Next, using the anisotropic conductive film produced in step g1, a chip with copper bumps (1.7 x 1.7 mm, thickness: 0.5 mm) and a substrate with copper bumps (thickness: 0.7 mm) were connected according to the steps i) to iii) below to obtain a connection structure. i) The separator (a silicone-treated polyethylene terephthalate film, 40 μm thick) on one side of the anisotropic conductive film (2 × 19 mm) is peeled off, and the anisotropic conductive film is brought into contact with the substrate with copper bumps, and the anisotropic conductive film is subjected to a pressure of 80°C, 0.98 MPa (10 kgf / cm 2 ) and pasted it in. ii) The separator on the other side was peeled off, and the copper-bumped chip was attached while aligning the bumps on the copper-bumped chip with the bumps on the copper-bumped substrate. Note that the flat surface of the solder particles was facing the copper-bumped substrate. iii) Heat and pressure were applied from above the chip under conditions of 180°C, 40 gf / bump, and 30 seconds to perform the permanent connection. A total of seven types of connection structures according to (1) to (7) were fabricated using the following combinations of "chip / anisotropic conductive film / substrate" (1) to (7). (1) Chip C1 / 40 μm thick conductive film / substrate D1 (2) Chip C1 / 24 μm thick conductive film / substrate D1 (3) Chip C1 / 16 μm thick conductive film / substrate D1 (4) Chip C2 / 16 μm thick conductive film / substrate D2 (5) Chip C3 / 12 μm thick conductive film / substrate D3 (6) Chip C4 / 8μm thick conductive film / substrate D4 (7) Chip C5 / 8μm thick conductive film / substrate D5

[0078] [Examples 2-36] Anisotropic conductive films and connection structures were produced in the same manner as in Production Example 1, except that the bases (transfer molds) having solder particles arranged in recesses obtained in Examples 2 to 36 were used.

[0079] [Comparative Preparation Example 1] A solder particle-containing anisotropic conductive paste was prepared containing the following components in the following parts by weight: Polymer: 12 parts by weight Thermosetting compound: 29 parts by mass High dielectric constant hardener: 20 parts by weight Heat curing agent: 11.5 parts by weight Flux-coated solder particles: 36 parts by weight (flux 2 parts by weight, solder particles 34 parts by weight)

[0080] The above polymer was prepared as follows. Synthesis of reaction product (polymer A) of bisphenol F with 1,6-hexanediol diglycidyl ether and bisphenol F-based epoxy resin: 72 parts by mass of bisphenol F (containing 4,4'-methylenebisphenol, 2,4'-methylenebisphenol, and 2,2'-methylenebisphenol in a mass ratio of 2:3:1), 70 parts by mass of 1,6-hexanediol diglycidyl ether, and 30 parts by mass of bisphenol F type epoxy resin (EPICLON EXA-830CRP manufactured by DIC Corporation) were placed in a three-neck flask and dissolved at 150°C under a nitrogen flow. Then, 0.1 parts by mass of tetra-n-butylsulfonium bromide, which is an addition reaction catalyst between hydroxyl groups and epoxy groups, was added, and an addition polymerization reaction was carried out at 150°C for 6 hours under a nitrogen flow to obtain a reaction product (polymer).

[0081] As the thermosetting compound, a resorcinol type epoxy compound, "EX-201" manufactured by Nagase ChemteX Corporation, was used.

[0082] As the high dielectric constant hardener, pentaerythritol tetrakis(3-mercaptobutyrate was used.

[0083] As the heat curing agent, "Karenz MT PE1" manufactured by Showa Denko K.K. was used.

[0084] The flux-coated solder particles were prepared as follows. 200 g of SnBi solder particles ("ST-3" manufactured by Mitsui Kinzoku Co., Ltd.), 40 g of adipic acid, and 70 g of acetone were weighed into a three-necked flask, and then 0.3 g of dibutyltin oxide, which is a dehydration condensation catalyst between the hydroxyl groups on the surface of the solder particle body and the carboxyl groups of adipic acid, was added and reacted at 60°C for 4 hours. The solder particles were then collected by filtration. The collected solder particles, 50 g of adipic acid, 200 g of toluene, and 0.3 g of paratoluenesulfonic acid were weighed into a three-necked flask, and reacted at 120°C for 3 hours while evacuating and refluxing. At this time, the reaction was carried out while removing water generated by dehydration condensation using a Dean-Stark extraction device. The solder particles were then collected by filtration, washed with hexane, and dried. The obtained solder particles were then crushed with a ball mill, and a sieve was selected so as to obtain a predetermined CV value. The obtained SnBi solder particles (flux-coated solder particles) had an average particle size of 4 μm and a CV value of 31%.

[0085] Using this solder particle-containing anisotropic conductive paste, a connection structure was produced by connecting a chip with copper bumps and a substrate with copper bumps in the same manner as in Production Example 1. The solder particle-containing anisotropic conductive paste was applied to the top of the substrate, and the chip was placed on top of the paste. The bumps of the chip with copper bumps and the bumps of the substrate with copper bumps were aligned, and heating and pressure were applied from above the chip under conditions of 180°C, 4gf / bump, and 30 seconds, to complete the main connection.

[0086] [Comparative Preparation Example 2] A solder particle-containing anisotropic conductive paste was prepared in the same manner as in Comparative Preparation Example 1, except that 200 g of SnBi solder particles ("Type-4" manufactured by Mitsui Kinzoku Co., Ltd.) was used instead of 200 g of SnBi solder particles ("ST-3" manufactured by Mitsui Kinzoku Co., Ltd.). The SnBi solder particles used had an average particle diameter of 26 μm and a CV value of 25%. A connection structure was prepared in the same manner as in Comparative Preparation Example 1, using the obtained solder particle-containing anisotropic conductive paste.

[0087] <Evaluation of connection structures> A conductive resistance test and an insulation resistance test were performed on some of the obtained connection structures as follows.

[0088] (Conductivity resistance test - Moisture absorption and heat resistance test) Regarding the conduction resistance between a chip (bump) with copper bumps and a substrate (bump) with copper bumps, the initial conduction resistance value and the value after a moisture absorption and heat resistance test (left for 100, 500, and 1000 hours under conditions of a temperature of 85°C and a humidity of 85%) were measured for 20 samples, and the average value was calculated. The conduction resistance was evaluated from the obtained average value according to the following criteria. The results are shown in Table 3. If the following criteria A or B were satisfied after 1000 hours of moisture absorption and heat resistance testing, the conduction resistance was deemed good. A: The average resistance is less than 2Ω B: The average resistance is between 2Ω and 5Ω C: The average resistance is between 5 Ω and 10 Ω D: The average resistance is 10 Ω or more and less than 20 Ω E: The average resistance is 20Ω or more

[0089] (Conductivity resistance test - high temperature storage test) The conduction resistance between the chip (bump) with copper bumps and the substrate (bump) with copper bumps was measured for samples before and after high-temperature storage tests (100, 500, and 1000 hours at 100°C). After high-temperature storage, a drop impact was applied, and the conduction resistance of the sample after the drop impact was measured. The drop impact was performed by fixing the connection structure to a metal plate with screws and dropping it from a height of 50 cm. After the drop, the DC resistance was measured at the solder joints (4 places) at the chip corners that received the greatest impact, and when the measured value increased by 5 times or more from the initial resistance, it was deemed that a break had occurred, and evaluation was performed. A total of 80 points were measured for 20 samples and 4 points. The results are shown in Table 4. The solder connection reliability was evaluated as good when the following criteria A or B were met after 20 drops. A: After 20 drops, none of the 80 solder joints showed a resistance increase of more than five times the initial resistance. B: After 20 drops, one to five solder joints had a resistance that was five times higher than the initial resistance. C: After 20 drops, 6 to 20 solder joints were found to have a resistance that was 5 times higher than the initial resistance. D: After 20 drops, 21 or more solder joints had resistance that was five times higher than the initial resistance.

[0090] (Insulation resistance test) Regarding the insulation resistance between the chip electrodes, the initial insulation resistance value and the value after migration testing (exposed for 100, 500, and 1000 hours under conditions of temperature 60°C, humidity 90%, and 20V application) were measured for 20 samples. 9 The percentage of samples with a resistance of 0.01Ω or more was calculated. The insulation resistance was evaluated based on the obtained percentage according to the following criteria. The results are shown in Table 5. If the following criteria A or B were met after 1000 hours of moisture absorption and heat resistance testing, the insulation resistance can be said to be good. A: Insulation resistance value 10 9 The percentage of Ω or higher is 100%. B: Insulation resistance value 10 9 The percentage of Ω or higher is between 90% and 100% C: Insulation resistance value 10 9 The percentage of Ω or higher is between 80% and 90% D: Insulation resistance value 10 9 The ratio of Ω or more is between 50% and 80% E: Insulation resistance value 10 9 The ratio of Ω or more is less than 50%

[0091] [Table 1]

[0092] [Table 2]

[0093] [Table 3]

[0094] [Table 4]

[0095] [Table 5]

[0096] <Examples 13-24> Anisotropic conductive films and connection structures were produced in the same manner as in Production Examples 1 to 12, except that solder particles and substrates produced in the same manner as in Examples 25 to 36 were used. The evaluation results are shown in Tables 6 to 8.

[0097] [Table 6]

[0098] [Table 7]

[0099] [Table 8]

[0100] <Example 37> Solder particles were produced, collected and evaluated in the same manner as in Example 13, except that in step b1, a base having a plurality of recesses with the cross-sectional shape shown in Figure 8 (approximate recess shape to Figure 4(b)), i.e., bottom diameter a of 0.6 μm, opening diameter b1 of 1.0 μm and opening diameter b2 of 1.2 μm (bottom diameter a: 1.0 μmφ is located in the center of opening diameter b2: 1.2 μmφ when viewing the opening from above). The results are shown in Table 10.

[0101] <Examples 38 to 48> Solder particles were produced, collected, and evaluated in the same manner as in Example 37, except that the size of the recessed portion was changed as shown in Table 9. The results are shown in Table 10.

[0102] [Table 9]

[0103] [Table 10]

[0104] In Examples 37 to 48, the cross-sectional shape of the recess narrows in multiple steps toward the bottom, so when the solder particles melt and coalesce, they tend to gather together in the recess, and fewer solder particles are left behind, which tends to lower the CV value. On the other hand, the bottom of the recess is larger than the flat portion formed on the surface of the solder particle, so the size of the flat portion does not change significantly. If the size of the bottom of the recess is made extremely small, it may affect the flat portion of the solder particle surface.

[0105] <Examples 25-24> Except for using the solder particles and bases prepared in the same manner as in Examples 37 to 48, anisotropic conductive films and connection structures were prepared in the same manner as in Preparation Examples 1 to 12. The evaluation results are shown in Tables 11 to 13.

[0106] [Table 11]

[0107] [Table 12]

[0108] [Table 13]

[0109] <Examples 49 to 51> Solder particles were prepared, collected, and evaluated in the same manner as in Example 13, except that in step a1, 10 g of Sn-Bi solder particles (manufactured by 5N Plus, melting point 139°C, Type 9) with an average particle size of 3.0 μm and a CV value of 32% were used, and in step b1, the recesses shown in Table 14 were used. The results are shown in Table 15.

[0110] <Examples 52 to 54> Solder particles were prepared, collected, and evaluated in the same manner as in Example 13, except that in step a1, 10 g of Sn-Bi solder particles (manufactured by 5N Plus, melting point 139°C, Type 10) with an average particle size of 2.8 μm and a CV value of 28% were used, and in step b1, the recesses shown in Table 14 were used. The results are shown in Table 15.

[0111] <Examples 55-57> In step a1, 100 g of In-Sn solder particles (5N Plus, melting point 120°C, Type 8) were immersed in distilled water, ultrasonically dispersed, and then allowed to stand, and the solder particles floating in the supernatant were collected. Solder particles with an average particle size of 1.0 μm and a CV value of 40% were used, in step b1, the recesses shown in Table 14 were used, and the following step c2 was performed instead of step c1. Except for this, solder particles were produced, collected, and evaluated in the same manner as in Example 13. The results are shown in Table 15. (Step c2) Formation of solder particles The substrate with the solder particles placed in the recesses in step b1 was placed in a hydrogen radical reduction furnace (plasma reflow device manufactured by Shinko Seiki Co., Ltd.), and after evacuation, hydrogen gas was introduced into the furnace to fill it with hydrogen gas. The temperature inside the furnace was then adjusted to 110°C, and hydrogen radicals were irradiated for 5 minutes. The hydrogen gas in the furnace was then removed by evacuation, and the furnace was heated to 160°C. After that, nitrogen was introduced into the furnace to return it to atmospheric pressure, and the temperature inside the furnace was then lowered to room temperature to form solder particles.

[0112] <Examples 58-60> In step a1, 100 g of Sn-Ag-Cu solder particles (5N Plus, melting point 219°C, Type 8) were immersed in distilled water, ultrasonically dispersed, and then allowed to stand, and the solder particles floating in the supernatant were collected. Solder particles with an average particle size of 1.0 μm and a CV value of 41% were used, in step b1, the recesses shown in Table 14 were used, and the following step c2 was performed instead of step c1. Except for this, solder particles were produced, collected, and evaluated in the same manner as in Example 13. The results are shown in Table 15. (Step c2) Formation of solder particles The substrate with the solder particles placed in the recesses in step b1 was placed in a hydrogen radical reduction furnace (plasma reflow device manufactured by Shinko Seiki Co., Ltd.), and after evacuation, hydrogen gas was introduced into the furnace to fill it with hydrogen gas. The temperature inside the furnace was then adjusted to 150°C, and hydrogen radicals were irradiated for 3 minutes. The hydrogen gas in the furnace was then removed by evacuation, and the furnace was heated to 240°C. After that, nitrogen was introduced into the furnace to return it to atmospheric pressure, and the temperature inside the furnace was then lowered to room temperature to form solder particles.

[0113] [Table 14]

[0114] [Table 15]

[0115] In this way, even if the solder particles have different sizes or are made of different materials, the method of the present invention can produce solder particles with a uniform particle size.

[0116] <Prototypes 37-39> Except for using the solder particles prepared in the same manner as in Examples 49 to 51, anisotropic conductive films and connection structures were produced in the same manner as in Prototype Example 1. The results are shown in Tables 16 to 18.

[0117] <Prototype Examples 40-42> Except for using the solder particles prepared in the same manner as in Examples 52 to 54, anisotropic conductive films and connection structures were produced in the same manner as in Prototype Example 1. The results are shown in Tables 16 to 18.

[0118] <Prototypes 43-45> Except for using the solder particles prepared in the same manner as in Examples 55 to 57, anisotropic conductive films and connection structures were produced in the same manner as in Prototype Example 1. The results are shown in Tables 16 to 18.

[0119] <Prototype Examples 46-48> Except for using solder particles prepared in the same manner as in Examples 58 to 60 and setting the main pressure bonding temperature to 230° C. in step 11, anisotropic conductive films and connection structures were produced in the same manner as in Example 1. The results are shown in Tables 16 to 18.

[0120] [Table 16]

[0121] [Table 17]

[0122] [Table 18]

[0123] The smaller the central particle diameter of the solder particles, the lower the CV value of the solder particles obtained after reduction and melting tends to be when the size of the recess is small (for example, 2 μm or 3 μm at the bottom). This is thought to be because the smaller the central particle diameter of the solder particles, the higher the filling rate into the recesses and the less variation in filling between multiple recesses. According to the method of the present application, solder particles with uniform particle diameters and different melting points can be easily obtained by simply changing the composition of the solder particles. In addition, various cross-sectional shapes of the recesses can be used. That is, the cross-sectional shape of the recesses can be appropriately selected according to the final use method and form of the solder particles. For example, when solder particles are dispersed in a resin to ensure fluidity like ink, it is considered preferable that the surface of the solder particles has a continuous curved surface. On the other hand, when solder particles are dispersed in a film and the solder particles are brought into contact with an electrode by a pressure bonding process, if the solder particles have a flat surface depending on the shape and material of the electrode, the impact on the electrode at the time of contact can be mitigated and the electrode can be prevented from being damaged. In addition, the resin whose viscosity has been reduced by heating in the pressure bonding process can flow and move from above the electrode, but when the resin has a flat surface, the contact area with the electrode is likely to be large, and the wetting of the electrode spreads quickly when the oxide film is removed by the flux, so there is an advantage that the movement due to the resin flow can be suppressed. The same phenomenon is also observed in resin paste. Furthermore, when the solder particles having a flat portion in a part obtained in the manufacturing example of the present application are transferred to an adhesive resin film or the adhesive resin is poured into a base to form a film, and then the base is removed, the orientation of the flat portion of the solder particles in the film can be aligned in approximately the same direction. When electrodes are pressure-mounted using such an adhesive resin film containing solder particles, the flat portion contacts the electrodes made of a very thin or weak material, so that electrode damage can be suppressed. In addition, even for electrodes that are difficult to spread wetly, the flat portion contacts the surface during pressure bonding, which has the advantage that wet spreading due to removal of the oxide film of the solder particles is more likely to occur than in spherical point contact. In practical use, the electrodes to be connected generally have different configurations and materials, and the feature of being able to roughly align the orientation of the flat portions of the solder particles, as in the present application, is characterized in that the position of the adhesive resin film can be selected according to the electrode material to achieve a more reliable connection.

[0124] <Examples 49-51> The solder particles obtained in Examples 46, 47, and 48 were placed on Au electrodes of 10 μm, 20 μm, and 50 μm in length and width formed by sputtering through masks with openings of 6 μm, 14 μm, and 40 μm, respectively. The substrate on which the Au electrode was formed was tilted at 15 degrees, 20 degrees, 30 degrees, and 45 degrees, and was struck with a metal spatula to apply vibration. After applying vibration, the electrode was observed, and the solder particles remaining on the electrode were particles whose flat parts were in contact with the Au electrode surface.

[0125] In this way, when solder particles are placed on an electrode, such as in a process such as BGA connection, the flat portion makes it difficult for the solder particles to move off the electrode due to vibrations, wind, etc. [Explanation of symbols]

[0126] 1...solder particle, 11...flat portion, 111...solder fine particle, 60...base, 60a...surface, 62...recess, 62a...bottom.

Claims

1. A solder particle having a flat portion on part of its surface.

2. 2. The solder particles according to claim 1, having an average particle size of 1 to 30 μm and a CV value of 20% or less.

3. The solder particle according to claim 1 or 2, wherein a ratio (A / B) of a diameter A of the flat portion to a diameter B of the solder particle satisfies the following formula: 0.01<A / B<1.0

4. The solder particle according to any one of claims 1 to 3, wherein when a rectangle circumscribing a projected image of the solder particle is created by two pairs of parallel lines, and the distances between the opposing sides are X and Y (where Y<X), X and Y satisfy the following formula: 0.8<Y / X<1.0

5. The solder particles according to any one of claims 1 to 4, comprising at least one selected from the group consisting of tin, a tin alloy, indium, and an indium alloy.

6. The solder particles according to claim 5, comprising at least one selected from the group consisting of an In-Sn alloy, an In-Sn-Ag alloy, an In-Bi alloy, a Sn-Au alloy, a Sn-Bi alloy, a Sn-Bi-Ag alloy, a Sn-Ag-Cu alloy, and a Sn-Cu alloy.

Citation Information

Patent Citations

  • Metal powder and paste thereof

    JP1989184201A

  • Method for forming metal ball

    JP1993023887A

  • Terminal connection structure, terminal connection method, manufacture of conductive particle, and manufacturing board

    JP1993082934A

  • Solder powder and solder paste

    JP2010036234A

  • Method for manufacturing mold for producing solder ball and method for producing solder ball

    JP2014058147A